2012
DOI: 10.1001/archneurol.2011.1658
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Diffusion in Vanishing White Matter

Abstract: To investigate the occurrence of restricted diffusion in vanishing white matter, the affected structures, the time of occurrence in the disease course, and the histopathologic correlate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…White matter cavitations are also seen in mitochondrial leukoencephalopathies (23,24), but cysts have well-delineated borders, which often display diffusion restriction and contrast enhancement. In VWM, the white matter cystic decay is more diffuse, contrast enhancement is absent (1,25), and diffusion restriction occurs in relatively preserved white matter (26). Radiating stripes within abnormal cerebral white matter are shared by VWM, metachromatic leukodystrophy, and Krabbe disease (1,27).…”
Section: Discussionmentioning
confidence: 99%
“…White matter cavitations are also seen in mitochondrial leukoencephalopathies (23,24), but cysts have well-delineated borders, which often display diffusion restriction and contrast enhancement. In VWM, the white matter cystic decay is more diffuse, contrast enhancement is absent (1,25), and diffusion restriction occurs in relatively preserved white matter (26). Radiating stripes within abnormal cerebral white matter are shared by VWM, metachromatic leukodystrophy, and Krabbe disease (1,27).…”
Section: Discussionmentioning
confidence: 99%
“…van der Lei, et al studied the DWI of 46 individuals suffering from VWM disease where it was observed that diffusion restriction occurred in younger patients with short disease course in areas of brain that were relatively unaffected by disease and had high cellularity. 5 Ding, et al reported the presence of diffusion restriction in six patients with VWM who had short disease duration of less than 12 months. 6 However, researchers opine that diffusion restriction is an uncommon feature of VWM and genetic confirmation is essential for establishing the diagnosis especially if the neuroimaging is atypical.…”
Section: Discussionmentioning
confidence: 99%
“…In Megalencephalic Leukoencephalopathy with subcortical Cysts the intramyelinic vacuoles are large and cause facilitated diffusion ( van der Voorn et al, 2006 ). In Vanishing White Matter, increased cellularity in relatively spared regions leads to restricted diffusion, whereas rarefied or cystic regions have facilitated diffusion ( van der Lei et al, 2012 ). In MLD, sulfatide accumulation in distended perivascular macrophages may result in white matter stripes with restricted diffusion ( Oguz et al, 2004 , Seidl et al, 2008 , Sener, 2003 , van Rappard et al, 2018b ).…”
Section: Quantitative Mrimentioning
confidence: 99%